2019
DOI: 10.1002/1878-0261.12443
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically modulated FOXM1 suppresses dendritic cell maturation in pancreatic cancer and colon cancer

Abstract: Forkhead box transcription factor M1 ( FOXM 1) is a proliferation‐associated transcription factor involved in tumorigenesis through transcriptional regulation of its target genes in various cells, including dendritic cells ( DC s). Although previous work has shown that FOXM 1 enhances DC maturation in response to house dust mite allergens, it is not known whether FOXM 1 affects DC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 42 publications
5
48
0
Order By: Relevance
“…It has also been shown that the FOXM1-PSMB4 axis can play a catalytic role in the proliferation and development of cervical cancer [28]. More surprisingly, FOXM1 plays a vital role in many other cancers [29][30][31][32]. In our study, FOXM1 was upregulated in tumor tissues compared to normal tissues, suggesting a signi cant correlation with melanoma.…”
Section: Discussionsupporting
confidence: 57%
“…It has also been shown that the FOXM1-PSMB4 axis can play a catalytic role in the proliferation and development of cervical cancer [28]. More surprisingly, FOXM1 plays a vital role in many other cancers [29][30][31][32]. In our study, FOXM1 was upregulated in tumor tissues compared to normal tissues, suggesting a signi cant correlation with melanoma.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, it has been shown that the FOXM1-PSMB4 axis can play a catalytic role in the proliferation and development of cervical cancer [28]. More surprisingly, FOXM1 plays a vital role in many other cancers [29][30][31][32]. In our study, FOXM1 was upregulated in tumor tissues compared to normal tissues, suggesting a signi cant correlation with melanoma.…”
Section: Discussionsupporting
confidence: 46%
“…Several pathways are involved in DC activation and/or tolerogenicity in both malignant and non-malignant conditions. In tumors, the dual state of both the proinflammatory and immunosuppressive microenvironment is well described [ 43 , 44 , 45 , 46 ]. Wnt5, a member of the Wnt family signaling pathway, which is wildly expressed by tumors and immune cells, activates the NFκB pathway and induces the tolerogenic phenotype via the release of IL-10 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt5, a member of the Wnt family signaling pathway, which is wildly expressed by tumors and immune cells, activates the NFκB pathway and induces the tolerogenic phenotype via the release of IL-10 [ 44 ]. Impaired DC functions and maturation due to Wnt5 upregulation was observed in pancreatic and colon cancer [ 46 ]. Besides tumors, Wnt5 signaling is activated in sepsis or acute respiratory distress syndrome as an initiator of the lung repair process [ 47 ].…”
Section: Discussionmentioning
confidence: 99%